Reporting interventions in trials evaluating cognitive rehabilitation in people with Multiple Sclerosis: a systematic review - Mhizha-Murira, Jacqueline R.; Drummond, Avril E.R.; Klein, Olga; das Nair, Roshan (SAGE, 2018)
Objective: To determine the quantity and quality of description of cognitive rehabilitation for cognitive deficits in people with Multiple Sclerosis, using a variety of published checklists, and suggest ways of improving the reporting of these interventions. Data sources: Ten electronic databases were searched, including MEDLINE, EMBASE, CINAHL and PsycINFO, from inception to May 2017. Grey literature databases, trials registers, reference lists and author citations were also searched. Review methods: Papers were included if participants were people with multiple sclerosis aged 18 years and over, and if the effectiveness of cognitive rehabilitation in improving functional ability for memory, attention or executive dysfunction, with or without a control group, was being evaluated. Results: Fifty-four studies were included in this review. The reporting of a number of key aspects of cognitive rehabilitation was poor. This was particularly in relation to content of interventions (reported completely in 26 of the 54 studies), intervention procedures (reported completely in 16 of the 54 studies), delivery mode (reported completely in 24 of the 54 studies) and intervention mechanism of action (reported completely in 21 of the 54 studies). Conclusion: The quality of reporting of cognitive rehabilitation for memory, attention and executive function for multiple sclerosis, across a range of study designs, is poor. Existing reporting checklists do not adequately cover aspects relevant to cognitive rehabilitation, such as the approaches used to address cognitive deficits. Future checklists could consider these aspects we have identified in this review.